A survey on recent notions of singularity for kernels of nonlinear integral operators - Mantellini, Ilaria; Bardaro, Carlo (Modern Mathematical Methods, 2026)
In this paper, we review several notions of singularity for kernels of abstract nonlinear integral operators acting on functions defined over locally compact Hausdorff topological spaces or groups. A recent general definition of abstract nonlinear operators is also discussed, which includes some discrete operators, as the sampling series in a nonlinear form.